2010
DOI: 10.1093/hmg/ddq508
|View full text |Cite
|
Sign up to set email alerts
|

Impaired minor tri-snRNP assembly generates differential splicing defects of U12-type introns in lymphoblasts derived from a type I SMA patient

Abstract: The survival of motor neuron (SMN) protein is essential for cytoplasmic assembly of spliceosomal snRNPs. Although the normal proportion of endogenous snRNAs is unevenly altered in spinal muscular atrophy (SMA) tissues, the biogenesis of individual snRNPs is not dramatically affected in SMN-deficient cells. The SMN protein is also required for normal Cajal body (CB) formation, but the functional consequences of CB disruption upon SMN deficiency have not yet been analyzed at the level of macromolecular snRNPs as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
106
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(115 citation statements)
references
References 44 publications
9
106
0
Order By: Relevance
“…This suggestion is supported by the tissue-specific defects seen in several genetic syndromes that are characterized by tri-snRNP insufficiency but are compatible with life. adRP, spinal muscular atrophy (SMA), and mandibulofacial dysostosis with microcephaly syndrome (MFDM) are heritable genetic syndromes that stem from heterozygous mutations or deletions in the SMN gene (SMA) or discrete tri-snRNP factors (adRP and MFDM) and consequently lead to haploinsufficiency and impaired tri-snRNP function (Boulisfane et al 2011;Tanackovic et al 2011;Lines et al 2012). Although these mutated splicing factors are ubiquitously expressed, defects are seen in specific cell types or tissues consistent with our data that some cells are more sensitive to perturbations in the tri-snRNP complex.…”
Section: Discussionmentioning
confidence: 99%
“…This suggestion is supported by the tissue-specific defects seen in several genetic syndromes that are characterized by tri-snRNP insufficiency but are compatible with life. adRP, spinal muscular atrophy (SMA), and mandibulofacial dysostosis with microcephaly syndrome (MFDM) are heritable genetic syndromes that stem from heterozygous mutations or deletions in the SMN gene (SMA) or discrete tri-snRNP factors (adRP and MFDM) and consequently lead to haploinsufficiency and impaired tri-snRNP function (Boulisfane et al 2011;Tanackovic et al 2011;Lines et al 2012). Although these mutated splicing factors are ubiquitously expressed, defects are seen in specific cell types or tissues consistent with our data that some cells are more sensitive to perturbations in the tri-snRNP complex.…”
Section: Discussionmentioning
confidence: 99%
“…7G-I). 51,[78][79][80][81] ALS is the most common adult-onset neurodegenerative disease affecting upper and lower motor neurons. Mutations in the RNA binding proteins FUS and TDP-43, involved in transcription and mRNA splicing and transport, are responsible for a subset of ALS cases.…”
Section: Cajal Bodies In Neuropathological Disordersmentioning
confidence: 99%
“…Several lines of evidence support CB dysfunction in motor neuron diseases: i) in postnatal and mature mammalian neurons SMN and coilin co-localize in typical canonical CBs (Figs. 4C, 6D, 7A), while Gems are not detected; 26,31 ii) in cell lines and mammalian nervous tissue, the formation and integrity of CBs are dependent on ongoing transcription and snRNP biogenesis, 7,57,59,92,93 2 nuclear functions altered in motor neuron diseases; 81,86,94 iii) lack of CBs in cells derived from SMA patients correlates with decreased U4/U6-U5 tri-snRNP assembly, a maturation step of spliceosomal snRNPs that is 10-fold faster in CBs than in nucleoplasm, 62,95 and with splicing alterations of particular minor introns; 78,80 iv) coilin protein, which is lacking in Gems, scaffolds CBs and couples snRNP and snoRNP biogenesis, making CBs the center of small non-coding RNA processing; 7,33,42 and v) in motor neurons of a 3-month-old SMA patient, we have observed that lowered SMN levels induce severe depletion of canonical CBs, whereas Gems were conspicuously absent in both SMA and age-matched control neurons (Fig. 7G-I).…”
Section: 96mentioning
confidence: 99%
“…Other examples of diseases that can arise because of impaired splicing of U12-type introns include spinal muscular atrophy (18,19) and Peutz-Jeghers syndrome (PJS), an intestinal polyposis syndrome that predisposes to cancer because of mutations in the tumor suppressor gene (TSG) LKB1 (liver kinase B1) (20). The observation that impaired U12-type splicing can affect TSG expression has interesting implications for other TSGs containing U12-type introns, such as PTEN (phosphatase and tensin homolog deleted on chromosome 10), where even a modest loss in PTEN function predisposes mice to cancer (21).…”
Section: Significancementioning
confidence: 99%